2009
DOI: 10.1515/znc-2009-9-1024
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of an Unusual 3-Hydroxyindole Derivative Isolated from Fruits of Aristotelia chilensis (Molina) Stuntz

Abstract: 3-Hydroxyindole was isolated from the EtOH extract of fruits of Aristotelia chilensis during analyses by HPLC/MS and GC/MS and identifi ed by its mass fragmentation pattern and spectrophotometric data. Additionally, this extract showed an interesting antioxidant activity in DPPH, crocin and TBARS assays. The presence of this type of compound in this fruit species permits us to explain its strong antioxidant activity and its important part in the biosynthetic pathway of phenolic and alkaloid compounds in this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
(21 reference statements)
0
8
0
Order By: Relevance
“… 23 , 91 , 98 While most analytical reports have concentrated on the chemical profiling of maqui berry phenolic compounds, mainly anthocyanins, using various analytical techniques coupled in some cases with some biological testing, reports on the isolation of secondary metabolites from the fruits are still scarce. 93 , 94 , 98 , 102 , 103 Among the few such studies is the isolation of 3-hydroxyindole, which was found to possess antioxidant capacity, 104 and the aforementioned bioactive delphinidin-3- O -sambuboside-5- O -glucopyranoside isolated from an anthocyanin-rich extract of maqui berry. 100 …”
Section: Maqui Berrymentioning
confidence: 99%
“… 23 , 91 , 98 While most analytical reports have concentrated on the chemical profiling of maqui berry phenolic compounds, mainly anthocyanins, using various analytical techniques coupled in some cases with some biological testing, reports on the isolation of secondary metabolites from the fruits are still scarce. 93 , 94 , 98 , 102 , 103 Among the few such studies is the isolation of 3-hydroxyindole, which was found to possess antioxidant capacity, 104 and the aforementioned bioactive delphinidin-3- O -sambuboside-5- O -glucopyranoside isolated from an anthocyanin-rich extract of maqui berry. 100 …”
Section: Maqui Berrymentioning
confidence: 99%
“…These results triggered recent studies and development of food, nutraceutical, cosmetical and pharmaceutical products (Avello et al, 2009;Céspedes et al, 2008Céspedes et al, , 2009Céspedes et al, , 2010Gironés-Vilaplana et al, 2012;Rubilar et al, 2011;Schreckinger et al, 2010), all of them based until now on wild crafted maqui berries with increasing exploitation.…”
Section: Introductionmentioning
confidence: 98%
“…Previously, it has been reported the alkaloid composition of the leaves of A. chilensis [16][17][18][19][20]. On the other hand, in the continuation of the general screening program of Chilean flora with biological activities [20], up-to-date several studies report that fruit extracts of A. chilensis possess several biological activities including antioxidant, cardioprotection, enzymes inhibition and as mediators in inflammation, among other activities [20][21][22][23][24][25][26][27]. It has been enjoyed as an ethno-medicine for many years, it is also used as an anti-inflammatory agent on kidneys pains, diverse digestive ailments (intestinal tumors and stomach ulcers), fever and cicatrization injuries, antiinflammatory effects, antioxidant properties, antiatherogenic, hypoglycemia, antihaemolytic, and inhibit LDL oxidation [28][29][30].…”
Section: Introductionmentioning
confidence: 99%